Microwave field-effect transistors theory, design, and applications - Pengelly, Raymond S. (Raymond Sydney) 1948- (Atlanta, GA Noble Publishing Corp., 1994)
The following topics are dealt with: GaAs FET theory-small signal; GaAs FET theory-power; requirements and fabrication of GaAs FETs; design of transistor amplifiers; FET mixers; GaAs FET oscillators; FET and IC packaging; FET circuits; gallium arsenide integrated circuits; and other III-V materials and devices.
Electronic reproduction.
Keywords: Gallium arsenide semiconductors; Metal semiconductor field-effect transistors; Electronic books